2015
DOI: 10.1111/jpc.12933
|View full text |Cite
|
Sign up to set email alerts
|

Sleep concerns in children and young people with cerebral palsy in their home setting

Abstract: Concerns about sleep vary across ages and GMFCS levels of children and young people with CP. Concerns relate to impairment of body structure and function, activity, environment, and personal supports. Multi-disciplinary, home-based assessment and interventions are recommended to address these concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
1
21
0
2
Order By: Relevance
“…Intervention strategies related to the clinical setting may in turn require educating healthcare professionals to improve their sleep knowledge, as well as adaptations on an organisational level in order for sleep to become a standard item for review during routine health assessments. Moreover, effective sleep assessment should be broad enough to screen for all kinds of sleep issues, yet focused enough to target specific individual parental concerns and needs [40]. This approach should result in healthcare-based interventions that are tailored to the unique and diverse family situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention strategies related to the clinical setting may in turn require educating healthcare professionals to improve their sleep knowledge, as well as adaptations on an organisational level in order for sleep to become a standard item for review during routine health assessments. Moreover, effective sleep assessment should be broad enough to screen for all kinds of sleep issues, yet focused enough to target specific individual parental concerns and needs [40]. This approach should result in healthcare-based interventions that are tailored to the unique and diverse family situations.…”
Section: Discussionmentioning
confidence: 99%
“…It may well be that parents of the most severely impaired children experienced a greater burden of care demands at night, with a greater impact on family functioning and wellbeing. Concerns about sleep have been found to vary across ages in children and young people with CP, but are present at every GMFCS level [40]. Despite the use of a convenience sampling method, we managed to reach great variation in age and GMFCS levels between children.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
“…In sleeping scores was found 13% of children with CP, and there was at least one abnormal score in sleep questionnaire in %35. Another study of Romeo et al (24) found that more than 40% of children with CP presented with at least one sleep disorder, and there was a relationship between sleep disturbance and GMFCS level V. McCabe et al (25) argued that several sleep problems exist in each GMFCS level. The children and adolescents with CP were reported to be affected by sleep disorders at any age and every GMFCS level (25).…”
Section: Among Those 52 Children With Sleep Problems Thementioning
confidence: 99%
“…Another study of Romeo et al (24) found that more than 40% of children with CP presented with at least one sleep disorder, and there was a relationship between sleep disturbance and GMFCS level V. McCabe et al (25) argued that several sleep problems exist in each GMFCS level. The children and adolescents with CP were reported to be affected by sleep disorders at any age and every GMFCS level (25). Hemmingsson et al (6) claimed that sleep problems are even more severe among children in GMFCS level IV and V. Adiga et al (26) reported that there was no significant correlation between GMFCS levels and sleep disorders.…”
Section: Among Those 52 Children With Sleep Problems Thementioning
confidence: 99%
“…(3,(9)(10)(11)(12)(13)(14) have explored the impact of the child's sleep problems on the parent. Again, there is a paucity of Australian based studies that specifically focus on CP, with only two published studies, a pilot (15) that led to the current study and a larger study, (16) which was a retrospective audit of children who attended a sleep service.…”
Section: Introductionmentioning
confidence: 99%